Factors Engendering Cost Misrepresentation of Public Sector Projects in Ghana - Asiedu, Richard Ohene; W. Alfen, Hans (International Journal of Sustainable Construction Engineering and Technology, 2014)
The main purpose of this research was to identify the core factors that engender construction cost overruns in public buildings in Ghana. Adopting a positivist, realist and value free philosophical approach, the research employs a multiple research strategy emphasized by the funnel technique principle. Twenty two dominant factors generated from a combination of exploratory interviews and extensive literature in the context of GCI was designed into a structured questionnaire targeting 240 clients, consultants and contractors. With a 55% return rate, the response of the participants were analysed using a combination of severity, frequency and relative importance indices. The five most important factors according to all three participants are (1) delay and uncertainty surrounding payment for work done (2) lack of enforcement of contract provisions by parties (3) variations and additional works resulting from changes in site conditions (4) lapses and challenges within PPL (5) excessive material and labour price fluctuations. Even though the Spearman’s rank correlation test showed a strong agreement between clients and consultants, there was however a weak correlation between clients and contractors and consultants and contractors which is normal considering the allegations and counter-allegations regarding each other’s contribution towards cost overruns. However a fair degree of objectivity and validity can be credited to the results considering the average level of experience of the respondents in the GCI.